Painted shark vertebrae beads from the Djawumbu–Madjawarrnja complex, western Arnhem Land. Issue 1 (2nd January 2016) - Wright, Duncan; Langley, Michelle C.; May, Sally K.; Johnston, Iain G.; Allen, Lindy
Abstract: In Europe and Africa, fine grained use wear and residue analyses of various organic bead technologies have provided remarkable information about specialist artisans and their affiliate communities. Ethnographic research suggests that personal ornaments represent one of the best ways to explore past human interactions and ethno-linguistic diversity. The study of material culture featured in rock art is now well established in Australia, but few detailed analyses have concentrated on personal ornaments recovered from the archaeological record. Fewer still have assessed the potential of this medium for assessing regional variations, despite rich ethnographic histories which point to the significance of these objects for self-differentiating communities and/or clans. This paper examines a collection of painted shark vertebrae beads recently discovered during archaeological survey in Arnhem Land. Detailed morphometric and use wear analysis is presented for these ornaments, alongside Aboriginal oral traditions, and assessment of similar artefacts held in museum collections across Australia. The potential of this combined approach within the Australian context is discussed, including how these studies add to our understanding of group signifying behaviour.